Sex-Related Abnormalities in Substantia Nigra Lipids in Parkinson's Disease. (June 2018) - Seyfried, T. N.; Choi, H.; Chevalier, A.; Hogan, D.; Akgoc, Z.; Schneider, J. S.
Parkinson's disease (PD) is a neurodegenerative movement disorder involving the selective loss of dopamine-producing neurons in the substantia nigra (SN). Differences in disease presentation, prevalence, and age of onset have been reported between males and females with PD. The content and composition of the major glycosphingolipids, phospholipids, and cholesterol were evaluated in the SN from 12 PD subjects and in 18 age-matched, neurologically normal controls. Total SN ganglioside sialic acid content and water content (%) were significantly lower in the male PD subjects than in the male controls. The content of all major gangliosides were reduced in the male PD subjects to some degree, but the neuronal-enriched gangliosides, GD1a and GT1b, were most significantly reduced. The distribution of phosphatidylethanolamine, phosphatidylcholine, and phosphatidylinositol was also significantly lower in the male PD subjects than in the male controls. However, the distribution of myelin-enriched cerebrosides and sulfatides was significantly higher in the male PD subjects than in the male controls suggesting myelin sparing in the male PD subjects. No elevation was detected for astrocytosis-linked GD3. These neurochemical changes provide evidence of selective neuronal loss in SN of the males with PD without robust astrocytosis. In contrast to the SN lipid abnormalities found in the male PD subjects, no significant abnormalities were found in the female PD subjects for SN water content or for any major SN lipids. These data indicate sex-related differences in SN lipid abnormalities in PD.